The Implications of Multiple Repeat Cesarean Deliveries on Maternal Morbidity - Esra Can; Süleyman Cemil Oğlak (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aimed to assess the obstetric outcomes of cesarean delivery (CD) in a cohort of pregnant women who had a history of four or more previous CDs and compared them with those who had a history of three or fewer previous CDs.